Eu não tenho o que escolher, não. Já está escolhido por eles! Estudo qualitativo sobre expectativas e exercício da autonomia de mulheres acerca da escolha da via de nascimento no Brasil - Gontijo, Bárbara Dias Rezende (2021)
Introduction: Childbirth care has undergone major changes over the years and physiological childbirth has given way to increasingly medicalized and interventionist care. The biomedical model contributed to women losing their autonomy and protagonism during childbirth. In this current model of obstetric, care most women do not have their birth route choices respected and there is a mismatch between the desire for vaginal birth and the outcome with a cesarean. Aims: Analyze the conceptions of pregnant women about their expectations related to the way of birth, as well as the exercise of autonomy in (not) choosing the way their children are born. Material and methods: Qualitative study, carried out from four focus groups, with 31 pregnant women primiparous and non-primiparous women, in four basic family health units in a city in Minas Gerais with high rates of cesarean section. We did lexical analysis through Word Cloud and Similitude Tree and analysis thematic-category. For the quantitative analysis of categorical variables, we performed word frequency calculation, descending hierarchical classification by similarity and factorial correspondence analysis. For qualitative analysis of categorical variables, we performed content analysis. Results: From the inference of four classes (health network; resources and technologies of health; expectations about the routes of birth and expectations about labor), we identified the pilgrimage of pregnant women due to the disarticulation of health services, the routine indication of unnecessary associated procedures to the excess of interventions and the doctor-centered care model as factors that influenced the decision of women about the route of birth. Women do not feel participative or respected when choosing the route of birth and their decisions are not based on the exercise of autonomy. The (non) choice of birth route it comes up against professional imposition, the lack of professional availability to accompany the labor and delivery, the fear of experiencing a bad experience and the fallacious indications for cesarean delivery. Because they have no choice, women opt for “cesarean on demand” in order to avoid obstetric violence. Exists a “limited autonomy”, exercised without prior knowledge of the risks and benefits of each mode of birth. Conclusions: The pilgrimage linked to the disarticulation of the health network, the excessive use of health resources and technologies, the excess of indications for cesarean sections and the low performance of obstetric nurses, made a positive birth experience impossible, in contrast to the expectations of women. From the perspective of parturients, the mode of birth is determined by the professionals who attend the birth and women have not exercised autonomy in this decision. There is a setback in the recognition of women's rights that makes it impossible to fully exercise autonomy in labor and birth.